Effect of cold plasma pretreated hot‐air drying on the physicochemical characteristics, nutritional values and antioxidant activity of shiitake mushroom. (21st May 2021) - Karim, Naymul; Shishir, Mohammad Rezaul Islam; Bao, Tao; Chen, Wei
Abstract: BACKGROUND: Shiitake mushroom is one of the most popular delicious vegetables, although fresh shiitake mushroom has short shelf life as a result of biochemical degradation. Drying can prolong the shelf life of mushroom. Additionally, application of cold plasma pretreatments (CPT) before drying can preserve the product quality, processing costs and nutritional values. Therefore, we aimed to explore the effect of cold plasma pretreated hot‐air drying at 50, 60 and 70 °C on the physicochemical characteristics, nutritional values and antioxidant activity of shiitake mushroom. RESULTS: Scanning electron microscopy micrographs showed that CPT induced the surface modification of fresh shiitake (such as cellular disarrangement, cellular shrinkages, disruption or break down of cell walls, and intracellular spaces and cavities) and facilitate the rapid drying than control samples. Furthermore, CPT improved the powder qualities (bulk density, water retention and swelling index) and preserved higher nutritional attributes (sugars, vitamins, phenolic acids contents and antioxidant activity) compared to the control groups. CONCLUSION: Conclusively, CPT could be a suitable alternative technique for improving drying characteristics and preserving nutritional attributes of agro‐based products. © 2021 Society of Chemical Industry.